Composite pollution remediation agent, preparation method and application thereof
Patent Information
- Application Number
- CN202511264306.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-09-05
AI Technical Summary
nZVI可通过吸附、催化还原及自由基氧化等机制降解有机污染物,但其在实际应用中仍面临易团聚、易氧化失活等问题
[0008]本发明的复合污染修复剂基于nZVI,利用生物炭负载nZVI,增加其分散性,从而减少团聚,提高nZVI的反应活性。引入β-环糊精作为空间位阻剂,也可以阻止nZVI的聚集,并将吸附到复合污染修复剂表面的微塑料与重金属富集到nZVI表面提高反应活性。再通过杂原子掺杂增强柯肯达尔(kirkendall)效应,促进nZVI表面纳米裂纹的形成,长期缓慢释放活性成分nZVI,延缓nZVI钝化,解决传统nZVI易失活的问题;并且能够形成Fe-P-C三元活性界面,提升复合污染修复剂抗氧化和电子转移能力,提升对复合污染的去除效果。
Smart Images

Figure CN120903598B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of environmental functional materials, and in particular to a composite pollution remediation agent, its preparation method, and its application in the removal of composite pollution. Background Technology
[0002] Microplastics, as an emerging environmental pollutant, are widely distributed in water, soil, and the atmosphere. Due to their high chemical stability and difficulty in degradation, traditional methods such as physical adsorption and biodegradation suffer from low removal efficiency, high cost, and the potential for secondary pollution. For example, activated carbon adsorption can only enrich microplastics but cannot completely degrade them; microbial degradation has a long cycle and is limited by environmental conditions; and advanced oxidation technologies (such as the Fenton process and persulfate advanced oxidation) may produce toxic intermediate products and are costly to treat. Especially for microplastics with a particle size of less than 100 μm, the removal efficiency of related remediation technologies is generally low. Furthermore, the coexistence of microplastics and heavy metals creates complex pollution that poses a serious threat to the ecological environment and human health. This complex pollution alters the environmental behavior and toxic effects of individual pollutants, causing more severe damage to ecosystems than single pollutants. Therefore, research on remediation technologies for complex pollution involving microplastics and heavy metals, as well as the development of remediation materials, is of great significance.
[0003] Nano-zero valent iron (nZVI) has shown great potential in the field of environmental pollution remediation due to its advantages such as high specific surface area, strong reducing power, and low cost. nZVI can degrade organic pollutants through mechanisms such as adsorption, catalytic reduction, and free radical oxidation, but it still faces problems such as easy aggregation and easy oxidation and deactivation in practical applications. Summary of the Invention
[0004] In view of this, in order to at least partially solve at least one of the aforementioned technical problems, the present invention provides a composite pollution remediation agent, its preparation method, and its application.
[0005] According to one aspect of the present invention, a composite pollution remediation agent is provided, comprising: biochar, and nZVI, cyclodextrin and heteroatoms supported on the biochar, wherein at least a portion of the nZVI is encapsulated within the cyclodextrin.
[0006] According to another aspect of the present invention, a method for preparing a composite pollution remediation agent is provided, comprising: mixing biochar in a mixed solution containing iron salt, cyclodextrin and heteroatom-containing reagent, adding a reducing agent under an inert atmosphere, stirring the reaction, and separating the composite pollution remediation agent by magnetic separation.
[0007] According to another aspect of the present invention, an application of a composite pollution remediation agent is provided, comprising using the composite pollution remediation agent to remove composite pollution of microplastics and heavy metals; the microplastics include at least one of polystyrene microplastics, polyethylene microplastics and polyvinyl chloride microplastics, and the heavy metals include at least one of Cd, As and Pb.
[0008] This invention relates to a composite pollution remediation agent based on nZVI. The nZVI is loaded with biochar to increase its dispersibility, thereby reducing aggregation and enhancing its reactivity. The introduction of β-cyclodextrin as a steric hindrance agent also prevents nZVI aggregation and enriches microplastics and heavy metals adsorbed onto the surface of the composite pollution remediation agent onto the nZVI surface, improving reactivity. Furthermore, heteroatom doping enhances the Kirkendall effect, promoting the formation of nanocracks on the nZVI surface, resulting in the long-term, slow release of the active ingredient nZVI, delaying nZVI passivation, and solving the problem of easy deactivation of traditional nZVI. It also forms an Fe-PC ternary active interface, enhancing the composite pollution remediation agent's antioxidant and electron transfer capabilities, thus improving the removal effect on complex pollution.
[0009] The composite pollution remediation agent of this invention has a simple preparation process, can effectively realize the resource utilization of solid waste, and has a removal efficiency of over 90% for microplastics and a removal rate of 100% for heavy metals. This composite pollution remediation agent has excellent performance and good application prospects, providing a practical solution for the treatment of composite pollution of microplastics and heavy metals, and demonstrating significant practical application value. Attached Figure Description
[0010] Figure 1 This is a schematic flowchart of the preparation method of the composite pollution remediation agent in an embodiment of the present invention;
[0011] Figure 2 The images show the removal effects of different composite pollution remediation agents on PVC microplastics in the embodiments of the present invention.
[0012] Figure 3 The diagram shows the removal effect of different composite pollution remediation agents on heavy metal Cd in the embodiments of the present invention.
[0013] Figure 4 This is a graph showing the chloride ion precipitation results in different composite pollution remediation agent / PVC microplastic systems in the embodiments of the present invention;
[0014] Figure 5 This is a graph showing the chloride ion release rate constants in different composite pollution remediation agent / PVC microplastic systems in the embodiments of the present invention;
[0015] Figure 6The figures show the N2 adsorption / desorption curves and total pore size distribution of different composite pollution remediation agents in the embodiments of the present invention.
[0016] Figure 7 The figures show the N2 adsorption / desorption curves and total pore size distribution of different composite pollution remediation agents in the embodiments of the present invention.
[0017] Figure 8 The image shows a scanning electron microscope (SEM) image of the composite pollution remediation agent prepared in Example 3 of this invention.
[0018] Figure 9 This is a SEM image of the composite pollution remediation agent prepared in Example 3 of the present invention after 25 days of reaction;
[0019] Figure 10 The energy dispersive X-ray spectrum (EDS) of the composite pollution remediation agent prepared in Example 3 of this invention;
[0020] Figure 11 This is a statistical graph showing the elemental content of the composite pollution remediation agent prepared in Example 3 of this invention using energy-dispersive X-ray spectroscopy. Detailed Implementation
[0021] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the invention. In the following detailed description, numerous specific details are set forth to provide a thorough understanding of the embodiments of the invention for ease of explanation. However, it will be apparent that one or more embodiments may be practiced without these specific details. Furthermore, descriptions of well-known structures and techniques are omitted in the following description to avoid unnecessarily obscuring the concept of the invention.
[0022] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention. The term "comprising" as used herein indicates the presence of features, steps, or operations, but does not exclude the presence or addition of one or more other features.
[0023] In realizing the concept of this invention, it was discovered that nZVI, due to its high specific surface area, strong reducing power, and low cost, shows great potential in the field of environmental pollution remediation. However, in practical applications, it still faces problems such as easy aggregation and easy oxidation and deactivation. Although bimetallic modification can significantly enhance the reduction effect of nZVI and provide some special reaction mechanisms, its easy aggregation problem also limits its application in pollutant removal. Therefore, this invention chooses biochar-supported nZVI, which can increase the dispersibility of nZVI and thus provide more active sites for pollutant reduction. β-Cyclodextrin can enrich the microplastics and heavy metals adsorbed on the surface of the composite pollution remediation agent onto the nZVI surface, thereby improving its reactivity. Heteroatom doping can also effectively improve the hydrophobicity of nZVI, thereby reducing its hydrogen evolution reaction with water and promoting the transfer of electrons from nZVI to pollutants, improving the electron selectivity of nZVI.
[0024] Specifically, according to one embodiment of the present invention, a composite pollution remediation agent is provided, comprising: biochar, and nZVI, cyclodextrin and heteroatoms supported on the biochar, wherein at least a portion of the nZVI is encapsulated within the cyclodextrin.
[0025] According to embodiments of the present invention, by combining biochar, nZVI, cyclodextrin and heteroatoms, a synergistic "adsorption-enrichment-degradation" system is constructed. Specifically, biochar adsorbs heavy metals, β-cyclodextrin captures microplastics, heteroatoms delay the passivation of nZVI, and nZVI degrades microplastics and heavy metals through a reductive dechlorination process. This provides a highly efficient, economical and sustainable solution for the treatment of combined pollution from microplastics and heavy metals.
[0026] According to embodiments of the present invention, nZVI can remove various pollutants from the environment through mechanisms such as catalytic reduction, adsorption, and free radical oxidation. Its reducing properties can directly or indirectly reduce pollutants through electron transfer, converting them into less toxic or easily removable forms. For example, many high-valence ions of heavy metals (such as Cd, Pb, Hg, Ag, etc.) have oxidizing properties and can be reduced by nZVI to low-valence or elemental states, and then removed through precipitation, adsorption, etc. nZVI can also break the C-Cl bonds in chlorinated organic compounds through electron transfer, achieving dechlorination reduction and generating low-chlorine or chlorine-free small-molecule organic compounds, significantly reducing their toxicity. nZVI is easily oxidized in aquatic environments, generating Fe... 2+ Fe 3+Plasma further forms iron oxides (such as FeO, Fe2O3), hydroxides (such as Fe(OH)2, Fe(OH)3), or hydroxyl oxides (such as FeOOH). These oxidation products have high specific surface areas and abundant surface functional groups (such as -OH), which can remove pollutants through adsorption, separating them from the water body and achieving the effect of purifying the aquatic environment. Under aerobic conditions, the corrosion process of nZVI may be accompanied by the generation of reactive oxygen species (ROS) (such as ·OH, O2). - These ROS (such as phenols, dyes, etc.) have strong oxidizing properties and can indirectly oxidize pollutants such as phenols and dyes.
[0027] According to embodiments of the present invention, biochar can increase the dispersibility of nZVI, thereby providing more active sites for the reduction of organic matter. In addition to improving the dispersibility of nZVI, the introduction of biochar can also enhance the hydrophobicity of nZVI, accelerate electron transfer, enhance the adsorption of pollutants, and form a micro-electrolysis system, thereby improving the ability of nZVI to remediate complex pollution.
[0028] According to embodiments of the present invention, the cyclodextrin is selected from at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, α-cyclodextrin polymer, β-cyclodextrin polymer, and γ-cyclodextrin polymer, preferably β-cyclodextrin.
[0029] According to embodiments of the present invention, biochar and cyclodextrin are synergistically loaded with nZVI. Cyclodextrin, acting as a molecular interface modifier, preferentially encapsulates hydrophobic pollutant microplastics through its unique hydrophobic cavity and hydrophilic outer wall structure, directionally delivering the target pollutant to the nZVI active site through a "molecular enrichment effect." Simultaneously, cyclodextrin also encapsulates nZVI, inhibiting its side reactions with oxygen and water (Fe2+). 0 +2H₂O→Fe 2+ +H2↑+2OH - 2Fe 0 +O2+2H2O→2Fe 2+ +4OH - The formation of cyclodextrin enhances the reactivity and long-lasting effect of nZVI. Cyclodextrin can also act as a steric hindrance agent, preventing the aggregation of nZVI and improving its reactivity.
[0030] According to embodiments of the present invention, the heteroatom is selected from at least one of nitrogen, phosphorus, and sulfur atoms, preferably phosphorus atoms.
[0031] According to embodiments of the present invention, heteroatoms enhance the Kirkendall effect by modulating the electronic structure of the composite pollution remediation agent, promoting the formation of nanocracks and significantly increasing the density of reactive sites. This allows for the long-term, slow release of the active ingredient nZVI, delaying nZVI passivation and solving the problem of easy inactivation of traditional nZVI. Furthermore, nanocracks can also enhance the electron transfer capability and antioxidant stability of nZVI, while optimizing the pollutant enrichment efficiency of cyclodextrin, achieving a synergistic improvement in material activity and lifespan, enabling the composite pollution remediation agent to possess both efficient degradation and controlled-release functions.
[0032] Figure 1 This is a schematic flowchart of the preparation method of the composite pollution remediation agent in an embodiment of the present invention.
[0033] According to another aspect of the present invention, a method for preparing a composite pollution remediation agent is provided, such as... Figure 1 As shown, it includes steps S1-S3.
[0034] Step S1: Mix the biochar in a mixed solution containing iron salts, cyclodextrins and heteroatom-containing reagents.
[0035] Step S2: Add a reducing agent under an inert atmosphere and stir to react.
[0036] Step S3: The composite pollution remediation agent is obtained by magnetic separation.
[0037] According to embodiments of the present invention, a long-acting composite pollution remediation agent based on controlled-release technology is constructed using a one-pot method on the basis of liquid-phase reduction. In-situ composite composition reduces the loss of physicochemical properties (such as oxidation and agglomeration) of components during multi-step preparation, improving the synergistic efficiency of each component. Compared to stepwise preparation, the one-pot method reduces energy consumption and raw material loss, making it suitable for large-scale production. The preparation method of the present invention can operate efficiently under ambient temperature and pressure conditions, and the process is simple and easy to control. The composite pollution remediation agent obtained after the reaction can be quickly recovered through magnetic separation, exhibiting advantages such as high removal efficiency and long-lasting effect on microplastics and heavy metals, and has significant engineering application value.
[0038] According to an embodiment of the present invention, prior to step S1, the method for preparing biochar includes: ball milling the cleaned and dried crab shells to obtain crab shell powder; and pyrolyzing the crab shell powder under an inert gas atmosphere to obtain biochar. Specifically, waste crab shells are repeatedly rinsed with deionized water until neutral to remove surface salts, protein residues, and attached contaminants, and then ultrasonically cleaned to remove deep impurities. They are then placed in a 60°C oven and dried for 12-14 hours until constant weight. The dried crab shells are then added to a ball mill for ball milling and passed through a 20-mesh sieve for later use. The grinding media used in the ball milling process are zirconia balls, with a weight ratio of zirconia balls to crab shells of 30-60:1, such as 30:1, 35:1, 45:1, 50:1, or 60:1. The ball milling speed is 200-600 rpm, such as 200 rpm, 300 rpm, 400 rpm, 500 rpm, or 600 rpm, and the ball milling time is 8-16 h, such as 8 h, 10 h, 12 h, 14 h, or 16 h. The sieved crab shell powder is placed in a crucible, compacted, and then placed in a tube furnace. It is then pyrolyzed at 500-900℃ for 2-6 h under an inert N2 atmosphere to obtain crab shell-based biochar. The preferred pyrolysis time is 4 h, and the pyrolysis temperature can be, for example, 500℃, 700℃, or 900℃.
[0039] According to embodiments of the present invention, a low-cost preparation process for environmentally friendly biochar materials was developed using waste crab shells as raw materials, combining low cost and environmental friendliness. Porous biochar (specific surface area >70 m²) was prepared via high-temperature pyrolysis. 2 By utilizing its three-dimensional hierarchical porous structure as a carrier and electron mediator for nZVI, this method not only solves the problem of solid waste disposal and realizes the high-value utilization of biochar resources, but also significantly reduces the preparation cost of composite pollution remediation agents and increases the possibility of site application. Simultaneously, it overcomes the defect of easy oxidation of traditional nZVI. The abundant oxygen-containing functional groups (such as carboxyl and hydroxyl groups) and defect sites of crab shell biochar not only effectively inhibit the aggregation of nZVI particles and significantly enhance the adsorption capacity for heavy metals, but also enhance the reactivity of composite pollution remediation agents through electron transfer.
[0040] According to embodiments of the present invention, such as Figure 1As shown, in step S1, the iron salt is selected from any one of divalent or trivalent iron salts, such as ferrous nitrate, ferrous sulfate, ferric nitrate, or ferric sulfate, preferably ferrous sulfate heptahydrate. The mass ratio of iron salt to biochar is 0.2-5:1, such as 0.2:1, 0.8:1, 1:1, 2:1, 3:1, 4:1, or 5:1, preferably 1:1. The mass ratio of biochar to cyclodextrin is 0.08-0.8:1, such as 0.08:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, or 0.8:1.
[0041] According to an embodiment of the present invention, in step S1, the heteroatom-containing reagent is selected from at least one of nitrogen-containing reagents, phosphorus-containing reagents, or sulfur-containing reagents. For example, it can be a combination of at least one or more of potassium dihydrogen phosphate, urea, phosphoric acid, dipotassium hydrogen phosphate, phytic acid, and thiourea. Preferably, it is a phosphorus-containing reagent potassium dihydrogen phosphate solution. The mass ratio of biochar to heteroatom-containing reagent is 0.2-2:1, for example, it can be 0.2:1, 0.4:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1, or 2:1.
[0042] According to an embodiment of the present invention, in step S1, the phosphorus-containing reagent as a dopant has a better effect on improving material performance and pollutant removal efficiency. Specifically, (1) Phosphorus-containing dopant can enhance electron transfer efficiency and reduce passivation: Sulfated nZVI usually forms a FeS shell, which can improve electron transfer, but after a long-term reaction, it may still passivate due to the thickening of the iron oxide shell. Phosphorated nZVI, by forming FePO4 or Fe-P bonded structures, not only promotes electron conduction, but also induces the Kirkendall effect during the reaction process, forming a nanocrack structure, continuously exposing fresh active sites, and delaying passivation. (2) Phosphorus-containing dopant can improve specific surface area and active site density: Phosphating modification can optimize the surface chemical properties of composite pollution remediation agents, increase hydroxyl (-OH) and phosphate (-PO4) functional groups, and enhance the coordination adsorption capacity for heavy metals. Compared with sulfated nZVI, the nanocrack structure of phosphated nZVI can provide more exposed Fe 0 Active sites enhance reaction kinetics. (3) Phosphorus-containing dopants can enhance pH adaptability and stability: nZVI sulfide is easily soluble under acidic conditions (FeS + 2H+). + →Fe 2+ +H2S), while the FePO4 structure of phosphating nZVI is more stable in a wide pH range (pH 4-10), making it suitable for complex aquatic environments. (4) Sulfate nZVI mainly removes Cd(II) through adsorption-reduction-coprecipitation, but there is competitive adsorption (such as competing with Pb(II) for active sites), which limits the removal rate of Cd(II). The phosphate group (PO4) of phosphating nZVI 3-Prioritize combining with Cd 2+ This process forms a stable Cd3(PO4)2 precipitate, reducing the impact of competitive adsorption. Therefore, this invention introduces P doping to form a Fe-PC ternary active interface, which can enhance the material's antioxidant and electron transfer capabilities, thereby improving the removal efficiency of complex pollutants.
[0043] According to an embodiment of the present invention, in step S2, the reducing agent is selected from either NaBH4 or KBH4, preferably NaBH4, and the molar ratio of its added amount to the iron salt added is 1-5:1, preferably 3:1; the stirring reaction time is 0.5-1.0 h, and the reaction temperature is 15-28℃, preferably 25℃.
[0044] According to an embodiment of the present invention, in step S2, NaBH4 acts as a strong reducing agent, releasing hydride anions (H+) in the aqueous solution. - ), to Fe 2+ Reduced to Fe 0 At the same time, it is oxidized to sodium metaborate (BO2). - The reducing agent releases heat upon contact with water, so it needs to be added slowly and at a low temperature (15-28℃). To prevent the oxidation of nZVI, N2 needs to be continuously introduced during the addition process.
[0045] According to an embodiment of the present invention, in step S3, the composite pollution remediation agent can be obtained by magnetic separation and freeze-drying of the reaction solution. The freeze-drying time is 12-24 h, for example, 12 h, 14 h, 18 h, 20 h, or 24 h; the temperature is -50 to -80℃, for example, -50℃, -60℃, -70℃, or -80℃.
[0046] According to an embodiment of the present invention, in step S3, nZVI has strong ferromagnetism and can be rapidly adsorbed and separated by an external magnetic field, while impurities, such as reducing agents and unreacted Fe, are separated. 2+ / Fe 3+ The decomposition products of NaBH4, etc., remain in the liquid phase due to their lack of magnetism. Freeze-drying is a crucial step in removing the reaction solvent, obtaining a dry composite remediation agent, and maximizing its dispersibility and activity.
[0047] According to another aspect of the present invention, an application of a composite pollution remediation agent is provided, comprising using the composite pollution remediation agent to remove composite pollution of microplastics and heavy metals; the microplastics include at least one of polystyrene microplastics, polyethylene microplastics and polyvinyl chloride microplastics, and the heavy metals include at least one of Cd, As and Pb.
[0048] According to embodiments of the present invention, the composite pollution remediation agent can effectively remove composite pollution of microplastics and heavy metals, providing a solution for the treatment of composite pollution that is both efficient, economical and sustainable.
[0049] According to embodiments of the present invention, the dosage of the composite pollution remediation agent in removing composite pollution is 0.5~5 g / L, for example, 0.5 g / L, 1 g / L, 2 g / L, 3 g / L, 4 g / L, or 5 g / L; the reaction time is 10-30 days, for example, 10 days, 20 days, or 30 days; the amount of microplastics added is 0.1%-1%, for example, 0.1%, 0.5%, or 1%; and the heavy metal concentration is 20-100 mg / L, for example, 20 mg / L, 50 mg / L, 80 mg / L, or 100 mg / L.
[0050] The present invention will now be described in further detail with reference to specific embodiments. The given embodiments are merely illustrative of the invention and not intended to limit its scope. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the invention in any way.
[0051] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0052] Preparation example:
[0053] The preparation method of biochar is shown in steps (1)-(3):
[0054] (1) Rinse the waste crab shells repeatedly with deionized water until neutral, then clean them with ultrasonic cleaning, and then dry them in a 60℃ oven for 12 h until constant weight.
[0055] (2) Add the dried crab shells from step (1) to a ball mill for ball milling and then pass them through a 20-mesh sieve to obtain crab shell powder.
[0056] (3) The crab shell powder sieved in step (2) is placed into a crucible, compacted and then placed in a tube furnace. It is then pyrolyzed at 500℃, 700℃ and 900℃ for 4 hours under N2 to obtain the corresponding biochar.
[0057] Example 1
[0058] (1) Compound pollution remediation agent CBC 500Preparation of -P-nZVI@β-CD: Weigh 2.482 g FeSO4·7H2O, 0.5 g biochar (crab shell powder pyrolyzed at 500℃), 1.5 g β-cyclodextrin (β-CD), and 0.659 g KH2PO4 into 500 mL of ultrapure water and mix. Transfer the mixture to a 1000 mL three-necked flask and stir for 2 h under N2 atmosphere to ensure thorough mixing. Simultaneously, prepare a NaBH4 solution (1.445 g dissolved in 300 mL of ultrapure water, three times the molar mass of Fe to ensure complete Fe reduction), and adjust the pH to 11 with 0.5 M NaOH. Using a peristaltic pump, slowly add the NaBH4 solution to the three-necked flask at a low speed of 10 rpm to fully reduce the iron salt to nZVI. After the addition is complete, continue stirring and aging for 30 min. Subsequently, after magnetic separation of the black precipitate, wash repeatedly with ultrapure water and ethanol, and freeze-dry for 12 h, the composite pollution remediation agent CBC can be obtained. 500 -P-nZVI@β-CD (phosphated nZVI encapsulated with β-cyclodextrin on 500℃ biochar carrier) is stored in an anaerobic chamber for later use.
[0059] (2) CBC 500 -P-nZVI@β-CD Degradation of Polyvinyl Chloride (PVC) Microplastics: PVC microplastics were selected as the characteristic pollutant, and the adsorption and degradation performance of the materials were tested. The PVC microplastic removal and degradation experiments were conducted in 100 mL headspace vials containing 100 mL of ultrapure water. The specific steps were as follows: First, 0.2% (w / w) of the added PVC microplastics (m0) was dispersed in 100 mL of ultrapure water. Subsequently, 200 mg (2 g / L) of CBC was added. 500 -P-nZVI@β-CD was capped with a PTFE-lined clamp cap and reacted in a horizontal shaking incubator (180 rpm) at 25±2℃. Samples were taken from the reaction mixture at specific time points (0, 1, 2, 4, 7, 10, 15, 20, 25 days), and nZVI was separated using magnetic separation. Subsequently, 1.5 mL of the supernatant was collected, filtered through a 0.45 μm PTFE membrane, and the filtered sample was placed in a 1.5 mL chromatographic vial to detect the release of Cl- from the system. - concentration.
[0060] On day 25, all supernatant was collected using magnetic separation. The water sample was vacuum filtered, and the filter membrane was carefully rinsed three times with ultrapure water. The membrane was then transferred to a glass petri dish and dried at 40°C. The dried sample was mixed with flotation solution (NaI) at a 1:3 ratio and shaken for 30 minutes. After standing for 30 minutes, PVC particles floated to the surface. The supernatant was aspirated using a glass syringe and vacuum filtered. The filter membrane was carefully rinsed three times with ultrapure water and transferred to a glass petri dish, then dried at 40°C. The dried sample was weighed (m), and the PVC microplastic removal efficiency was calculated. ).
[0061] (3) CBC 500 -P-nZVI@β-CD Degradation of Heavy Metal Cd: Heavy metal Cd was selected as the characteristic pollutant, and the adsorption and degradation performance of the material were tested. The heavy metal Cd adsorption experiment was conducted in a 100 mL headspace vial, and the specific steps are as follows: Prepare 50 mg·L⁻¹ solution... -1 Cd 2+ Transfer 100 ml of the solution to a 100 mL headspace vial and add CBC. 500 -P-nZVI@β-CD(2 g·L -1 The reaction mixture was capped with a PTFE-lined clamp and placed in a horizontal shaking incubator (180 rpm) at 25±2℃. Samples were taken from the reaction mixture at specific time points (0, 0.25, 0.5, 1, 2, 4, 6 h) and the remediation materials were separated using magnetic separation. Subsequently, 1.5 mL of the supernatant was collected, filtered through a 0.45 μm PTFE membrane, and the filtered sample was placed in a 1.5 mL chromatographic vial for Cd determination. 2+ Remaining concentration.
[0062] Example 2
[0063] The preparation method and pollutant removal method are consistent with those in Example 1, except that the pyrolysis temperature of the biochar is 700℃, resulting in the composite pollution remediation agent CBC. 700 -P-nZVI@β-CD.
[0064] Example 3
[0065] The preparation method and pollutant removal method are consistent with those in Example 1, except that the pyrolysis temperature of the biochar is 900℃, resulting in the composite pollution remediation agent CBC. 900 -P-nZVI@β-CD.
[0066] Example 4
[0067] The preparation method and pollutant removal method are consistent with those in Example 3, except that Na2S2O4 (0.329 g) is used as a heteroatom-containing dopant to obtain the composite pollutant remediation agent CBC. 900 -S-nZVI@β-CD.
[0068] Figure 10 The energy dispersive X-ray spectrum (EDS) of the composite pollution remediation agent prepared in Example 3 of this invention; Figure 11 This is a statistical graph showing the elemental content of the composite pollution remediation agent prepared in Example 3 of this invention using energy-dispersive X-ray spectroscopy.
[0069] according to Figure 10 It can be seen that CBC 900 -P-nZVI@β-CD has been successfully p-doped with a doping level of 12.14 wt%. Figure 11 ).
[0070] The removal rates of heavy metal Cd, PVC microplastics, Cl- precipitation amount, and precipitation rate constants in Examples 1-4 are shown in Table 1 below:
[0071] Table 1
[0072]
[0073] Figure 2 The images show the removal effects of different composite pollution remediation agents on PVC microplastics in the embodiments of the present invention. Figure 3 The diagram shows the removal effect of different composite pollution remediation agents on heavy metal Cd in the embodiments of the present invention. Figure 4 This is a graph showing the chloride ion precipitation results in different composite pollution remediation agent / PVC microplastic systems in the embodiments of the present invention; Figure 5 This is a graph showing the chloride ion release rate constants in different composite pollution remediation agent / PVC microplastic systems in the embodiments of the present invention; Figure 7 The figures show the N2 adsorption / desorption curves and total pore size distribution of different composite pollution remediation agents in the embodiments of the present invention.
[0074] As shown in Table 1, the different composite pollution remediation agents prepared in Examples 1-4 all achieved a removal rate of over 80% for PVC microplastics. Figure 2 The removal rate of heavy metal Cd was 100%. Figure 3 In Example 3, Cl was present in the system. - The highest precipitation amount ( Figure 4 The precipitation rate constant is the largest ( Figure 5 This indicates that the high-temperature carbonization temperature of biochar is a key factor affecting the degradation ability of the composite material. Biochar carbonized at 900℃ exhibits a highly graphitized structure and abundant mesoporous structures. Figure 7This significantly enhances electron transfer efficiency and facilitates the PVC dechlorination reaction. Furthermore, P doping outperforms S doping in overall performance by enhancing electron transfer, optimizing interfacial reactions, and improving stability.
[0075] Comparative Example 1
[0076] (1) Preparation of nZVI: 2.482 g of FeSO4·7H2O was weighed and dissolved in 500 mL of ultrapure water, and then transferred to a 1000 mL three-necked flask. The mixture was stirred for 1 h under a N2 atmosphere. At the same time, a NaBH4 solution was prepared (1.445 g dissolved in 300 mL of ultrapure water, three times the molar mass of Fe, to ensure that Fe was fully reduced). The pH was adjusted to 11 with 0.5 M NaOH. The NaBH4 solution was slowly added to the three-necked flask at a low speed of 10 rpm using a peristaltic pump to fully reduce the iron salt to nZVI. After the addition was complete, the mixture was stirred and aged for 30 min. Subsequently, the black precipitate was separated by magnetic separation, washed multiple times with ultrapure water and ethanol, and freeze-dried for 12 h to obtain the nZVI material, which was stored in an anaerobic chamber for later use.
[0077] (2) The pollutant removal method of Comparative Example 1 is the same as that of Example 1.
[0078] Comparative Example 2
[0079] The preparation method and pollutant removal method are consistent with those in Example 3, except that β-cyclodextrin and KH2PO4 are not added during the preparation process, resulting in CBC. 900 -nZVI.
[0080] Comparative Example 3
[0081] The preparation method and pollutant removal method are consistent with those in Example 3, except that KH2PO4 is not added during the preparation process, resulting in CBC. 900 -nZVI@β-CD.
[0082] Comparative Example 4
[0083] The preparation method and pollutant removal method are consistent with those in Example 3, except that β-cyclodextrin is not added during the preparation process, resulting in CBC. 900 -P-nZVI.
[0084] The removal rates of heavy metal Cd, PVC microplastics, and Cl in Example 3 and Comparative Examples 1-4 - The precipitation amount and precipitation rate constant are shown in Table 2 below:
[0085] Table 2
[0086]
[0087] Figure 6 The figures show the N2 adsorption / desorption curves and total pore size distribution of different composite pollution remediation agents in the embodiments of the present invention. Figure 8 The image shows a scanning electron microscope (SEM) image of the composite pollution remediation agent prepared in Example 3 of this invention. Figure 9 This is a SEM image of the composite pollution remediation agent prepared in Example 3 of the present invention after 25 days of reaction.
[0088] As shown in Table 2, compared with Comparative Examples 1-4, the PVC removal efficiency in Example 3 was significantly lower. Figure 2 ) and Cl - Precipitation amount ( Figure 4 The highest value indicates that biochar, β-CD, and P doping all played key roles in the degradation process, and the pyrolytic biochar at 900℃ provided a highly graphitized conductive network and abundant mesoporous structure. Figure 6 This significantly improved electron transfer efficiency and pollutant adsorption capacity; β-CD selectively enriched PVC microplastics through molecular inclusion and directionally transported them to nZVI active sites; P doping enhanced the Kirkendall effect and promoted the formation of nanocracks. Figure 8 The material maintains its stability even after 25 days of reaction. Figure 9 The synergistic effect of biochar, β-CD, and P doping significantly enhanced the antioxidant stability of nZVI. The combined effect of biochar, β-CD, and P doping promoted the efficient removal of PVC and Cl. - This maximizes the precipitation of nZVI, enhances its stability and activity, and improves its environmental adaptability.
[0089] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. The application of a composite pollution remediation agent, characterized in that, include: The composite pollution remediation agent is used to remove composite pollution from microplastics and heavy metals. The microplastics include at least one of polystyrene microplastics, polyethylene microplastics and polyvinyl chloride microplastics, and the heavy metals include at least one of Cd, As and Pb; The composite pollution remediation agent comprises: biochar, and nano-zero-valent iron, cyclodextrin, and heteroatoms supported on the biochar, wherein at least a portion of the nano-zero-valent iron is encapsulated within the cyclodextrin; and the heteroatoms are phosphorus atoms. The preparation method of the composite pollution remediation agent includes: mixing biochar in a mixed solution containing iron salt, cyclodextrin and heteroatom-containing reagent, adding a reducing agent under an inert atmosphere, stirring and reacting, and obtaining the composite pollution remediation agent by magnetic separation; The method for preparing the biochar includes: ball milling the cleaned and dried crab shells to obtain crab shell powder; and pyrolyzing the crab shell powder under an inert gas atmosphere to obtain biochar. The inert gas used in the pyrolysis process is N2, the pyrolysis time is 2-6 hours, and the pyrolysis temperature is 500-900℃.
2. The application according to claim 1, characterized in that: The cyclodextrin is selected from at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, α-cyclodextrin polymer, β-cyclodextrin polymer, and γ-cyclodextrin polymer.
3. The application according to claim 1, characterized in that: The reducing agent is selected from either NaBH4 or KBH4; The stirring reaction time is 0.5-1.0 h, and the reaction temperature is 15-28℃.
4. The application according to claim 1, characterized in that, The iron salt is selected from either divalent or trivalent iron salts; The heteroatom-containing reagent is a phosphorus-containing reagent.
5. The application according to claim 1, characterized in that: The heteroatom-containing reagent is selected from at least one of potassium dihydrogen phosphate, phosphoric acid, dipotassium hydrogen phosphate, and phytic acid.
Citation Information
Patent Citations
Application of beta-cyclodextrin embedded S-nZVI material
CN111437800A
Preparation method and application of slow-release iron-carbon composite material
CN118255426A
Biochar-nano iron-based composite material for repairing organic pollution and application of biochar-nano iron-based composite material
CN118894586A
